Bladder Lesions in Cystoscopic Bladder Biopsies-A Clinicopathological Study - Sedhain, Sapana; Dhakal, Sushil; Poudyal, Punam; Pradhan, Anju; Upadhyay, Paricha; Agrawal, Chandra Shekhar (Birat Journal of Health Sciences, 2023)
Introduction: In urinary bladder lesions, the clinical presentation is quite variable, the nonneoplastic lesions can mimic neoplastic and vice-versa bothering both clinicians and patients. The present study aims to study the clinic-pathological and histological features of various lesions of the urinary bladder in the specimens received through cystoscopic biopsy or transurethral resection.Objectives: The objectives of this study were to study the clinicopathological features of various bladder lesions and their frequencies and to correlate the clinical diagnosis with histological diagnosis.Methodology: The study was a descriptive cross-sectional involving patients with urinary bladder lesions requiring cystoscopic biopsy or transurethral resection conducted in the Department of Pathology of BP Koirala Institute of Health Sciences, Dharan over a period of one year (November 2016 to October 2017) .Results: Among 40 patients, mean age was 56.40 years and male and female ratio was 1.5:1. The mean duration of symptoms was 3.49 months. The most common presenting feature for both neoplastic and non-neoplastic was 75%, but hematuria was (86.36%) presenting feature in neoplastic cases and dysuria (88.88%) in non-neoplastic with each group accounting 55% and 45% respectively. Urothelial carcinoma (86.36%) was the commonest neoplastic lesion while cystitis (72.22%) was the commonest non-neoplastic lesion. NMIBC was the predominant lesion (78.95%) in urothelial tumor. Grading showed low grade (63.15%) and high grade (36.85%) respectively. The correlation analysis between clinical diagnosis and histological diagnosis revealed perfect correlation for non-neoplastic lesions and strong correlation for neoplastic  lesions having highly significant result (p